Nouvelles données paléoenvironnementales dans le Sud de la France vers 30000 ans 14C BP : le cas de la grotte Marie (Hérault) - Crochet, Jean-Yves; Gence, Jean; Boulbes, Nicolas; Boutié, Paul; Cretin, Catherine; Crégut-Bonnoure, Évelyne; Duzer, Danièle; Jolly, Dominique; Laudet, Frédéric; Lefévre, David; Mourer-Chauviré, Cécile; Rousselières, France; et al. (Comptes Rendus Palevol, 2007)
The Marie cave, discovered to the north of Montpellier, Herault (France), has yielded a fauna of 28 vertebrates, out of which 23 are small ´ to large mammals, notably Mammuthus primigenius. The few discovered artefacts have been attributed to the Upper Palaeolithic, which is in agreement with the two radiocarbon dates (31450 14 C yr BP for the low level, and 28680 14 C yr BP near the cave’s entrance). The palynological study shows the existence (i) of a wooded steppe on the plateau, and (ii) of a riverine forest with alders in the valleys, associated with Mediterranean taxa. These data conﬁrm the presence in Languedoc of Mediterranean species around 30000 yr BP, which qualiﬁes the hypothesis of exclusively Spanish and Italian refuges during glacial periods
Keywords: France; Marie cave; Palaeoenvironment; palynology; Upper Palaeolithic; Vertebrates; Wurm